The return of inequality : social change and the weight of the past - Savage, Michael, 1959- (Cambridge, Massachusetts : Harvard University Press, 2021)
"A pioneering book that takes us beyond economic debate to show how inequality is returning us to a past dominated by empires, dynastic elites, and ethnic divisions. The economic facts of inequality are clear. The rich have been pulling away from the rest of us for years, and the super-rich have been pulling away from the rich. More and more assets are concentrated in fewer and fewer hands. Mainstream economists say we need not worry; what matters is growth, not distribution. In The Return of Inequality, acclaimed sociologist Mike Savage pushes back, explaining inequality's profound deleterious effects on the shape of societies. Savage shows how economic inequality aggravates cultural, social, and political conflicts, challenging the coherence of liberal democratic nation-states. Put simply, severe inequality returns us to the past. By fracturing social bonds and harnessing the democratic process to the strategies of a resurgent aristocracy of the wealthy, inequality revives political conditions we thought we had moved beyond: empires and dynastic elites, explosive ethnic division, and metropolitan dominance that consigns all but a few cities to irrelevance. Inequality, in short, threatens to return us to the very history we have been trying to escape since the Age of Revolution. Westerners have been slow to appreciate that inequality undermines the very foundations of liberal democracy: faith in progress and trust in the political community's concern for all its members. Savage guides us through the ideas of leading theorists of inequality, including Marx, Bourdieu, and Piketty, revealing how inequality reimposes the burdens of the past. At once analytically rigorous and passionately argued, The Return of Inequality is a vital addition to one of our most important public debates"--
Introduction: What is the challenge of inequality? -- Part 1. Locating inequality in time and space -- Turning the telescope: the economic analysis of income distribution -- Society as a sports field: the challenge of Bourdieu -- Renewing Marx: capital accumulation and the weight of history -- Part 2. Inequality, empire, and the decline of nations -- The ranking of nations -- The return of empire: inequality on a global scale -- Insiders and outsiders: class, gender and race in historical perspective -- Visceral inequality in the 21st century -- Cities and accumulation -- The force of information and technology -- Part 3. The politics of inequality in the twenty-first century -- Reinstating the time of politics -- What is to be done?
Includes bibliographical references and index.
Keywords: Income distribution -- History -- 21st century; Equality -- 21st century; Regression (Civilization) -- 21st century; Social change -- 21st century